PARTISIPASI PETANI PADI DALAM PELAKSANAAN PROGRAM PENINGKATAN PRODUKSI BERAS NASIONAL (P2BN) DI KECAMATAN SEPUTIH MATARAM LAMPUNG TENGAH - Yama, I Made Thresna; Gitosaputra, Sumaryo; Hasanuddin, Tubagus (Jurnal Ilmu-Ilmu Agribisnis, 2018)
This study aims to find out the performance of the P2BN Program, to find out the level of rice farmers’ participation in the P2BN Program and to study the factors that influence the rice farmer participation in the P2BN Program. The research method used is a survey. The location is determined intentionally in subdistricts Seputih Mataram Central Lampung regency in November - December 2016.  Sample units are 95 rice farmers. The analyses of data used descriptive method and used Rank-Spearman correlation to test the hypothesis. The results of the research showed that: the performance of P2BN Program in planning, implementation, profit utilization, and evaluation in Seputih Mataram Subdistrict of Central Lampung Regency is in high classification, The level of rice farmer participation in P2BN Program is in middle classification.  Factors significantly related to farmers’ participation in implementation of P2BN Program are knowledge on P2BN Program and social support.  Meanwhile, the large of arable land, income level, and facility received by farmers do not have relationship with their participation in the P2BN Program.Key words: P2BN Program,  participation, Seputih Mataram